Analisis Tata Kelola Keuangan Desa Bandar Tengah - Zulia Almaida Siregar; Bahrudi Effendi; Ika Purnama Sari (AKUA: Jurnal Akuntansi dan Keuangan, 2023)
Related to the regional autonomy policy, this makes the village government have to be independent in managing the resources that they have in the village. Local governments are demanded to be independent in managing the village resources they have well. The village government must be able to manage these funds in an accountable and transparent manner. This study aims to determine the governance system in managing Village Funds and to assess the accountability and transparency of Village Fund management in Bandar Tengah Village, Bandar Khalipah District. This study used a qualitative approach with descriptive data analysis. Minister of Home Affairs Regulation Number 20 of 2018 is an indicator used to assess accountability and transparency. The results of the study show that the governance system for managing Village Funds in Bandar Tegah Village for the 2021 fiscal year is in accordance with applicable laws and regulations, namely the Minister of Home Affairs Regulation Number 20 of 2018. Accountability for managing Village Funds in Bandar Tegah Village consists of several stages, namely planning stage, implementation stage, administration stage, reporting stage, and accountability stage. All stages can be carried out properly. For the planning stage, it is carried out properly and follows the applicable rules and regulations, so that the management of village funds at this stage is accountable and transparent because the community is involved in the process.